Analisa Perspektif Tenaga Kesehatan Mengenai Aplikasi untuk Pencegahan dan Penanganan COVID-19 di Indonesia - Renya Vitalia Pasangka; Dedi Nugroho; Benny Efendie; Rizky Farmasita B. (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The Covid-19 pandemic that has hit Indonesia has had many impacts on various sectors. This virus is able to spread quickly so that the number of confirmed positives is increasing every day. In the era of the industrial revolution 4.0, currently all sectors are directed to digital services, including the health sector through health service applications. However, the implementation of health-based applications certainly has pros and cons, for this reason this study aims to find out the opinions of health workers regarding the application of handling and preventing Covid-19. This research uses qualitative research methods with library research research instruments and interviews. The results of the study show that in general, health workers do not need applications for handling Covid-19 due to the intensity of work for Covid-19 survivors and also the lack of knowledge of health workers in the field of digital health services or what we commonly call telemedical applications. However, the health workers who are the subjects of the interview are open to applications that contain prevention as well as the features contained in the PeduliLindung application. Healthcare workers also argue that apps can help with close contact tracing.